An observational study on non-communicable disease risk factors among healthcare workers in high-stress environments - Pirrello, Alessandra; Mancuso, Daniele Giacomo; Pace, Chiara; Immordino, Angelo; Meli, Virginia; Tramuto, Fabio; Casuccio, Alessandra; Immordino, Palmira (Frontiers in Public Health, 2025)
IntroductionNon-communicable diseases (NCDs) account for 74% of global mortality and place significant socioeconomic burdens on healthcare systems. Despite their knowledge and awareness, healthcare workers (HCWs) often struggle to adopt preventive measures due to demanding work conditions and high-stress environments.MethodsThis observational study aimed to evaluate the prevalence of NCD risk factors among HCWs at the University Hospital “Paolo Giaccone” in Palermo, Italy. An online questionnaire, based on the WHO’s STEPS approach, was administered to 390 HCWs. Data from 273 responses were analyzed using SPSS software.ResultsThe sample comprised 57.9% women, predominantly nurses (35.9%).DiscussionKey findings revealed that 56.8% consumed alcohol, 42.1% used tobacco, and 86.1% frequently skipped meals due to work. Lifestyle factors, such as fruit and vegetable consumption, salt intake, and physical activity, were assessed alongside metabolic risk factors like blood pressure, glycemia, and triglycerides. Despite their expertise in NCD prevention, HCWs often failed to implement healthy behaviors. While evening shift work showed limited correlation with lifestyle changes, results underscored the need for targeted health promotion programs for HCWs. Healthcare institutions should actively support their workforce in adopting healthier lifestyles to mitigate NCD risks and improve public health outcomes.